Latin-American consensus on the transition into adult life of patients with X-linked hypophosphatemia (2024)
Introduction X-linked hypophosphatemia is an orphan disease of genetic origin and multisystem involvement. It is characterized by a mutation of the PHEX gene which results in excess FGF23 production, with abnormal renal and intestinal phosphorus metabolism, hypophosphatemia and osteomalacia secondary to chronic renal excretion of phosphate. Clinical manifestations include hypophosphatemic rickets leading to growth abnormalities and osteomalacia, myopathy, bone pain and dental abscesses. The transition of these patients to adult life continues to pose challenges to health systems, medical practitioners, patients and families. For this reason, the aim of this consensus is to provide a set of recommendations to facilitate this process and ensure adequate management and follow-up, as well as the quality of life for patients with X-linked hypophosphatemia as they transition to adult life. Materials and Methods Eight Latin American experts on the subject participated in the consensus and two of them were appointed as coordinators. The consensus work was done in accordance with the nominal group technique in 6 phases: (1) question standardization, (2) definition of the maximum number of choices, (3) production of individual solutions or answers, (4) individual question review, (5) analysis and synthesis of the information and (6) synchronic meetings for clarification and voting. An agreement was determined to exist with 80% votes in favor in three voting cycles. Results and Discussion Transition to adult life in patients with hypophosphatemia is a complex process that requires a comprehensive approach, taking into consideration medical interventions and associated care, but also the psychosocial components of adult life and the participation of multiple stakeholders to ensure a successful process. The consensus proposes a total of 33 recommendations based on the evidence and the knowledge and experience of the experts. The goal of the recommendations is to optimize the management of these patients during their transition to adulthood, bearing in mind the need for multidisciplinary management, as well as the most relevant medical and psychosocial factors in the region.